DISTRIBUTION OF TRACE ELEMENTS IN TRAPS OF THE SOUTHERN SIBERIAN PLATFORM - Feoktistov G.D. (My University, 2003)
The distribution of trace elements (Li, Rb, Cu, Zn, Pb, Sn, Ag, Au, and Hg) was studied in trap sills of two intrusive phases in the southern Siberian Platform. Cluster and factor analyses of the composition of 86 trap samples show that most of the trace elements accumulated in the more silicic products of in-chamber magmatic differentiation. Rb and Li concentrations correlate with the K2O concentration; Pb and Sn, with SiO2; and Cu and Zn, with FeO. Ag, Au, and Hg concentrations do not correlate with the concentrations of major elements. Variations of the trace-element concentrations in traps of the southern Siberian Platform are comparable to those in traps (flood basalts) of some other igneous provinces of the world.